Fluorophore labeled gold nanorod and method for manufacturing the same
By depositing a silicone layer containing fluorescent dye on the surface of the gold nanorod, the problem of difficulty in using low-energy near-infrared light to excite the photosensitizer far away from the gold nanorod is solved in the prior art, and the fluorescent labeling of the gold nanorod in the visible light range is realized, which improves its application potential in biological systems.
Patent Information
- Application Number
- JP2023161653
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
The prior art has difficulty using low-energy near-infrared light to excite photosensitizers far away from gold nanorods, resulting in limited application in biological systems.
The fluorescently labeled gold nanorods are formed by depositing a silicone layer on the surface of the gold nanorods and spreading a fluorescent dye containing a photosensitizer in the silicone layer. This method ensures that the fluorescent dye is evenly distributed in the silica gel layer by mixing on the NaOH solution contacting the gold nanorods and the MeOH solution of fluorescent dye, and remixing after adding the MeOH solution containing alcoholoxysilone.
The fluorescent labeling of gold nanorods in the visible light range is realized, which improves the reactive oxygen generation efficiency of the photosensitizer, especially under low-energy near-infrared light, which significantly improves its application potential in biological systems.
Smart Images

Figure 2025052767000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to fluorescently labeled gold nanorods and a method for producing the same. [Background technology]
[0002] Most of the photosensitizers developed to date generate reactive oxygen species when excited by visible light. The excitation light of such photosensitizers overlaps with the light absorption region of hemoproteins such as hemoglobin and water, so the excitation light has low biological permeability and there are limitations to its use.
[0003] One solution that is currently attracting attention is the use of near-infrared light, which is known as the "biological window" and has high transmittance through living organisms.
[0004] Gold nanoparticles have attracted attention for their unique optical properties in the visible light region, and are therefore of potential use as nanomaterials for bioimaging, contrast agents, labeling agents, biosensors, and even photothermal nanotherapeutics.
[0005] Among these gold nanoparticles, gold nanorods, which are rod-shaped gold nanoparticles, have wavelengths of light absorption and scattering that can be extended to the near-infrared region (550-1400 nm) that is transparent to biological tissues, making them useful for application in bioscience. However, there are concerns about the shape stability of gold nanorods in the nano-sized region, and quenching phenomena due to light energy transfer near interfaces make it difficult to use them as highly sensitive luminescent agents.
[0006] Patent Document 1 discloses fluorescently labeled silica-coated gold nanorods whose fluorescence intensity does not decrease, achieved by introducing a silane coupling agent into the silica layer of gold nanorods that have been silica-coated with tetraalkoxysilane and then binding a fluorescent substance to the silane coupling agent. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication No. 2021-110734 Summary of the Invention [Problem to be solved by the invention]
[0008] However, with the spacer technique disclosed in Patent Document 1, it is difficult to excite the photosensitizer separated from the gold nanorod by the spacer with low-energy light. [Means for solving the problem]
[0009] The inventors conducted research into silica-coated gold nanorods that efficiently generate active oxygen when exposed to low-energy light by applying a silica coating to the interface of gold nanorods in the presence of a fluorescent dye containing a photosensitizer, and completed the present invention.
[0010] [1] The object of the present invention is to Gold nanorods, a silica layer covering the entire gold nanorod; the silica layer comprises a fluorescent dye; the fluorescent dye is dispersed throughout the silica layer; Fluorescently labeled gold nanorods The purpose of this project is to provide
[0011] The fluorescently labeled gold nanorods of the present invention are capable of emitting fluorescence.
[0012] [2] The fluorescent dye may be a cationic fluorescent dye or a neutral fluorescent dye, and the fluorescent labeled gold nanorod may be as described in [1].
[0013] [3] The cationic fluorescent dye is α,β,γ,δ-tetrakis(1-methylpyridinium-4-yl)porphyrin p-toluenesulfonate (TMPyP) or its central metal complex, or rhodamine 6G (R6G); The neutral fluorescent dye is 7-diethylamino-4-methylcoumarin (Coumarin 1). The fluorescently labeled gold nanorod may be as described in [2].
[0014] [4] Another object of the present invention is to A composition comprising the fluorescently labeled gold nanorod described in [1]. The purpose of this project is to provide
[0015] Compositions containing photolabeled gold nanorods according to the present invention are capable of emitting fluorescence.
[0016] [5] The fluorescent dye is α,β,γ,δ-tetrakis(1-methylpyridinium-4-yl)porphyrin p-toluenesulfonate (TMPyP) or a central metal complex thereof, The composition is a composition for generating singlet oxygen by irradiation with excitation light. The composition may be as described in [4].
[0017] [6] Another object of the present invention is to A mixing step of mixing gold nanorods, alkoxysilane, and a fluorescent dye, The method for producing fluorescently labeled gold nanorods according to [1] The purpose of this project is to provide
[0018] The production method of the present invention makes it possible to produce fluorescently labeled gold nanorods.
[0019] [7] The mixing step comprises: a first sub-mixing step of mixing the NaOH solution in which the gold nanorods are dispersed and the MeOH solution in which the fluorescent dye is dispersed; a second sub-mixing step of mixing the first mixed solution obtained in the first sub-mixing step with the MeOH solution in which the alkoxysilane is dissolved; The method may be as described in [6],
[0020] [8] The mixing step may be the method described in [7], further comprising, after the second sub-mixing step, a warming and standing step of standing the second mixed solution obtained by the second sub-mixing step under a temperature condition of 20°C to 30°C for 12 to 36 hours. [Brief description of the drawings]
[0021] [Figure 1] Figures 1A to 1C show the FE-SEM images of SilicaAuNR@TMPyP, SilicaAuNR@R6G, and SilicaAuNR@Coumarin 1, respectively. [Diagram 2] Figure 2A shows the fluorescence spectrum of SilicaAuNR@TMPyP (excitation wavelength: 424 nm). Figure 2B shows the fluorescence spectrum of SilicaAuNR@R6G (excitation wavelength: 528 nm). Figure 2C shows the fluorescence spectrum of SilicaAuNR@ Coumarin 1 (excitation wavelength: 375 nm). [Diagram 3] Figure 3A shows a photograph of SilicaAuNR@TMPyP before (upper row) and after (lower row) ultraviolet irradiation. Figure 3B shows a photograph of SilicaAuNR@R6G before (upper row) and after (lower row) ultraviolet irradiation. Figure 3C shows a photograph of SilicaAuNR@ Coumarin 1 before (upper row) and after (lower row) ultraviolet irradiation. [Figure 4] Figure 4 shows a graph plotting the change in absorbance at 416 nm when TMPyP and SilicaAuNR@TMPyP were irradiated with light using a light irradiation device equipped with each optical filter (Y-50 (500 nm ≦), R-60 (600 nm ≦), and R-66 (660 nm ≦)). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] definition For convenience, certain terms used in this application are collected here. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. The singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise.
[0023] The numerical ranges and parameters given in the present invention are approximate values, but the numerical values given in the specific examples are described as precisely as possible. However, any numerical value inherently contains a certain error that necessarily results from the standard deviation found in each test measurement. Also, the term "about" as used herein generally means within 10%, 5%, 1% or 0.5% of a given value or range. Alternatively, the term "about" means within an acceptable standard error as considered by those skilled in the art.
[0024] Hereinafter, an embodiment of the present invention will be described. The following embodiment is merely an example, and the scope of the present invention is not limited to the following embodiment. Note that, in order to avoid repetition and complexity, explanations of similar contents will be omitted.
[0025] Fluorescently labeled gold nanorods The fluorescently labeled gold nanorods according to this embodiment include a gold nanorod and a silica layer that covers the entire gold nanorod. The silica layer contains a fluorescent dye that is dispersed throughout the entire silica layer.
[0026] The purity of the gold nanorods used in this embodiment is 75, 80, 85, 90, 95, 98, 99, 99.9, 99.99% or more, and may be within a range between any two of the numerical values exemplified here. The long axis of the gold nanorods used in this embodiment is 3, 10, 18, 32, 100, 180, 280, 400, 540, 800 nm, and may be within a range between any two of the numerical values exemplified here. The short axis of the gold nanorods used in this embodiment is 2, 5, 6, 8, 20, 30, 40, 50, 60, 80 nm, and may be within a range between any two of the numerical values exemplified here. The aspect ratio (long axis / short axis) of the gold nanorods used in this embodiment is 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, and may be within a range between any two of the numerical values exemplified here. The long and short axes of the gold nanorods can be measured from photographs taken with a scanning electron microscope.
[0027] In this embodiment, the average particle size of the gold nanorods is 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 nm, and may be within a range between any two of the numerical values exemplified here. The average particle size of the gold nanorods refers to the particle size at 50% of the integrated value in the particle size distribution obtained by measuring the diameter of the circle equivalent to the projected area of 200 particles randomly selected using a photograph taken by a scanning electron microscope. The average particle size of the gold nanorods may be calculated using a dynamic light scattering particle size distribution analyzer (DLS).
[0028] In this embodiment, the thickness of the silica layer covering the entire gold nanorod is 15, 20, 25, 30, 35, 40, or 45 nm, and may be within a range between any two of the numerical values exemplified here. The thickness of the silica layer can be measured from a photograph taken by a scanning electron microscope. The coverage of the silica layer with respect to the gold nanorod is 60, 70, 80, 90, 95, 98, 99, 99.9, or 99.99% or more, and may be within a range between any two of the numerical values exemplified here. The coverage of the silica layer can be calculated from the length of the portion of the gold nanorod coated with silica per entire circumference of the gold nanorod measured from a photograph taken by a scanning electron microscope. The gold nanorod is covered with a silica layer to stabilize the shape in the nano-sized region. The silica layer covering the gold nanorods can be produced by coating the surface of the gold nanorods with silica using an alkoxysilane (e.g., methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, dimethoxydiphenylsilane, n-propyltrimethoxysilane, hexyltrimethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltriethoxysilane, hexyltriethoxysilane, octyltriethoxysilane).
[0029] Fluorescent dyes In this embodiment, the fluorescent dye is dispersed throughout the silica layer. As described below, the silica layer according to this embodiment is formed on the gold nanorods in a solution containing TEOS and the fluorescent dye, so that the fluorescent dye is dispersed throughout the silica layer from the gold nanorod side of the silica layer to the outer surface side of the silica layer. The fluorescent dye according to this embodiment is a cationic fluorescent dye or a neutral fluorescent dye.
[0030] Cationic fluorescent dyes Cationic fluorescent dyes include α,β,γ,δ-tetrakis(1-methylpyridinium-4-yl)porphyrin p-toluenesulfonate (TMPyP) and its central metal complexes, and rhodamine 6G (R6G). TMPyP has the following chemical formula: [ka] It can be expressed as: R6G has the following chemical formula: [ka] It can be expressed as:
[0031] Neutral fluorescent dyes Neutral fluorescent dyes include 7-diethylamino-4-methylcoumarin (Coumarin 1). Coumarin 1 has the following chemical formula: It can be represented as TIFF2025052767000004.tif4545.
[0032] In an embodiment, the fluorescent dye is TMPyP or a central metal complex thereof. The metal in the central metal complex of TMPyP may be copper (Cu), zinc (Zn), magnesium (Mg), cobalt (Co), manganese (Mn), lead (Pb), mercury (Hg), cadmium (Cd), iron (Fe), palladium (Pd), nickel (Ni), aluminum (Al), silicon (Si), vanadium (V), platinum (Pt) or gold (Au). Since TMPyP or its central metal complex is a porphyrin derivative, it can generate singlet oxygen, which is one of the active oxygen species, by light irradiation. As shown in the examples described later, gold nanorods covered with a silica layer containing TMPyP or its central metal complex maintained singlet oxygen generating ability even in the visible light region of 500 nm or more, and also showed clear singlet oxygen generating ability by low-energy light excitation of 660 nm or more. Gold nanorods covered with a silica layer containing TMPyP or its central metal complex had a higher singlet oxygen generation efficiency when irradiated with low-energy light than TMPyP alone or its central metal complex alone, and are therefore expected to be effective in killing cancer tissue, decomposing stain components, and exerting antibacterial effects.
[0033] Composition or pharmaceutical composition comprising fluorescently labeled gold nanorods The fluorescently labeled gold nanorods can also be provided as a composition. The composition includes fluorescently labeled gold nanorods comprising gold nanorods and a silica layer covering the entire gold nanorods, the silica layer containing a fluorescent dye, and the fluorescent dye is dispersed throughout the silica layer. In one embodiment, the composition is a pharmaceutical composition. The pharmaceutical composition may be a pharmaceutical composition for treating, preventing, or slowing the progression of a tumor. In one embodiment, the composition is a composition for decomposing a dirt component. In another embodiment, the composition is an antibacterial composition. In yet another embodiment, the composition is a composition for generating singlet oxygen by irradiating excitation light. The excitation light may be light having a wavelength in the near infrared region (600, 650, 700, 750, 800, 850, and 900 nm, within a range between any two of the numerical values exemplified here). The excitation light may be light from which a specific wavelength (for example, a wavelength less than 500 nm) has been cut.
[0034] Method for producing fluorescently labeled gold nanorods The method for producing fluorescently labeled gold nanorods according to the present embodiment includes a mixing step of mixing gold nanorods, alkoxysilane, and a fluorescent dye. The gold nanorods may be commercially available gold nanorods or gold nanorods obtained by the method for producing gold nanorods described below.
[0035] Mixing Step In the mixing step, the gold nanorods, the alkoxysilane, and the fluorescent dye are mixed together, so that the gold nanorods are entirely covered with a silica layer containing the fluorescent dye. The gold nanorods, the alkoxysilane, and the fluorescent dye may be mixed together while being stirred.
[0036] The concentration ratio of gold nanorods to NaOH during the mixing step may be 1:0.8 to 1.5 (0.8, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or may be within a range between any two of the numerical values exemplified here).
[0037] The concentration ratio of gold nanorods to fluorescent dye during the mixing step may be 1:0.1 to 1.5 (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, and may be within a range between any two of the values exemplified here).
[0038] The concentration ratio of gold nanorods to alkoxysilane during the mixing step may be 1:3-15 (3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or may be within a range between any two of the numerical values exemplified here).
[0039] First Sub-Mixing Step and Second Sub-Mixing Step The mixing step may include a first sub-mixing step of mixing a NaOH solution having gold nanorods dispersed therein with a MeOH solution having a fluorescent dye dispersed therein, and a second sub-mixing step of mixing the first mixed solution obtained by the first sub-mixing step with a MeOH solution having alkoxysilane dissolved therein.
[0040] In the second sub-mixing step, the MeOH solution in which the alkoxysilane is dissolved may be added to the first mixed solution in 2 to 4 portions every 20 to 40 minutes.
[0041] The MeOH solution used in the first sub-mixing step and the second sub-mixing step may be a 20, 22, 24, 26, 28, or 30% MeOH solution, and may be within a range between any two of the numerical values exemplified herein. The stirring time in the second sub-mixing step may be 10, 15, 20, 25, 30, 35, or 40 minutes, and may be within a range between any two of the numerical values exemplified herein.
[0042] Incubation step The mixing step may further include, after the second sub-mixing step, a heating and standing step in which the second mixed solution obtained by the second sub-mixing step is allowed to stand under a temperature condition of 20°C to 30°C (20, 22, 24, 26, 28, and 30°C, and may be within a range between any two of the numerical values exemplified herein) for 12 to 36 hours (12, 18, 24, 30, and 36 hours, and may be within a range between any two of the numerical values exemplified herein).
[0043] Manufacturing steps to produce gold nanorods The method for producing fluorescently labeled gold nanorods according to this embodiment may include a production step of producing gold nanorods.
[0044] The steps for producing gold nanorods include, for example, a seed solution preparation step, a primary growth solution preparation step, and a secondary growth solution preparation step.
[0045] Seed Solution Preparation Step The core solution preparation steps include a first core solution preparation step of providing a hexadecyltrimethylammonium bromide (CTAB) solution, a second core solution preparation step of adding a potassium bromide solution to the CTAB solution, a third core solution preparation step of adding a chloroauric (III) acid solution to the mixed solution obtained in the second core solution preparation step, a fourth core solution preparation step of mixing an aqueous sodium borohydride solution with the mixed solution obtained in the third core solution preparation step while stirring, and a fifth core solution preparation step of leaving the mixed solution obtained in the fourth core solution preparation step to stand under temperature conditions of 20 to 40°C for 30, 45, 60, 75, or 80 minutes within a range between any two of the numerical values exemplified here.
[0046] The core solution preparation step may include a core solution preparation standing step, following the fourth core solution preparation step, in which the mixed solution obtained in the fourth core solution preparation step is allowed to stand for 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 minutes, within a range between any two of the numerical values exemplified here.
[0047] In the nuclei solution preparation step, the concentration ratio of CTAB to potassium bromide is 1:0.05 to 0.15 (0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, and may be within a range between any two of the numerical values exemplified here). In the nucleus solution preparation step, the concentration ratio of CTAB to gold(III) chloride is 1:0.001 to 0.003 (0.0015, 0.0016, 0.0017, 0.0018, 0.0019, 0.0020, 0.0021, 0.0022, 0.0023, 0.0024, 0.0025, 0.0026, 0.0027, 0.0028, 0.0029, 0.0030, and may be within a range between any two of the numerical values exemplified here). In the nucleus solution preparation step, the concentration ratio of CTAB to sodium borohydride is 1:0.001 to 0.010 (0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.010, and may be within a range between any two of the numerical values exemplified here).
[0048] Primary Growth Solution Preparation Steps The first growth solution preparation step includes a first growth solution preparation step of providing a CTAB solution, a second growth solution preparation step of adding a potassium bromide solution to the CTAB solution, a third growth solution preparation step of adding a silver nitrate (I) solution to the mixed solution obtained in the second growth solution preparation step, a fourth growth solution preparation step of adding a chloroauric (III) acid solution to the mixed solution obtained in the third growth solution preparation step, a fifth growth solution preparation step of adding an L-ascorbic acid solution to the mixed solution obtained in the fourth growth solution preparation step, and a fifth growth solution preparation step of adding a nucleus solution (nucleus solution) to the mixed solution obtained in the fifth growth solution preparation step. and a sixth step of preparing the first growth solution by adding and stirring the mixture.
[0049] In the first growth solution preparation step, the concentration ratio of CTAB to potassium bromide is 1:0.05 to 0.15 (0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to silver nitrate (I) is 1:0.001 to 0.003 (0.0015, 0.0016, 0.0017, 0.0018, 0.0019, 0.0020, 0.0021, 0.0022, 0.0023, 0.0024, 0.0025, 0.0026, 0.0027, 0.0028, 0.0029, 0.0030, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to gold (III) chloride is 1:0.005-0.015 (0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to L-ascorbic acid is 1:0.005-0.015 (0.005, 0.006, 0.007, 0.008, 0.009, 0.010, 0.011, 0.012, 0.013, 0.014, 0.015, and may be within a range between any two of the numerical values exemplified here). In the first growth solution preparation step, the concentration ratio of CTAB to gold in the nucleus solution is 1:0.5×10-6 to 5.5×10-6 (0.5×10-6, 1.5×10-6, 2.0×10-6, 2.5×10-6, 3.0×10-6, 3.5×10-6, 4.0×10-6, 4.5×10-6, 5.0×10-6, 5.5×10-6, and may be within a range between any two of the numerical values exemplified here).
[0050] Secondary Growth Solution Preparation Step The second growth solution preparation step includes a first growth solution preparation step in which an L-ascorbic acid solution is added to the first growth solution at an inflow rate of 0.5 to 2.0 mL / h (0.50, 0.75, 1.00, 1.25, 1.50, 1.75, 2.00, 2.25, 2.50, 2.75, 3.00 mL / h, within the range between any two of the numerical values exemplified herein) while stirring the mixed solution (first growth solution) obtained in the sixth growth solution preparation step; a second growth solution preparation step in which the mixed solution obtained in the first growth solution preparation step is stirred for 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 minutes, within the range between any two of the numerical values exemplified herein; and a third growth solution preparation step in which the mixed solution obtained in the second growth solution preparation step is allowed to stand for a time period of 12, 18, 24, 30, or 36 hours, within the range between any two of the numerical values exemplified herein.
[0051] In the second growth solution preparation step, the concentration ratio of gold to ascorbic acid in the first growth solution is 1:0.1 to 1.0 (0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, and may be within a range between any two of the numerical values exemplified here).
[0052] In addition, the manufacturing method of gold nanorods and the coating method of gold nanorods with silica can be found in JP 2018-127699 A. EXAMPLES
[0053] 1. Synthesis of Hexadecyltrimethylammonium Bromide-Protected Gold Nanorods Hexadecyltrimethylammonium bromide (CTAB) protected gold nanorods (CTAB-AuNR) were synthesized according to the following method.
[0054] Sample preparation Nuclear solution preparation (Au seed solution) ·125 mM CTAB (cetyl trimethylammonium bromide) aq. 364.45 mg (1.0 mmol) of CTAB was dissolved in 8.0 mL of milliQ. 100 mM KBr aq. 119.00 mg (1.0 mmol) of KBr was dissolved in 10.0 mL of milliQ. 2.4 mM HAuCl4·4H2O aq. 4.6 mM HAuCl4·4H2O aq. was diluted with milliQ. 10 mM NaBH4aq. 3.78 mg (0.10 mmol) of NaBH4 was dissolved in 10.0 mL of ice-cold milliQ.
[0055] Primary Growth Solution Preparation 125 mM CTAB aq. 3.43 g (9.4 mmol) of CTAB was dissolved in 77 mL of milliQ. 940 mM KBr aq. 1.12 g (9.4 mmol) of KBr was dissolved in 10.0 mL of milliQ. 19.2 mM AgNO3aq. 2.62 mg (0.192 mmol) of AgNO3 was dissolved in 10.0 mL of milliQ. 4.6 mM HAuCl4·4H2O aq. 105 mM AA (ascorbic acid) aq. 184.94 mg (1.05 mmol) of AA was dissolved in 10.0 mL of milliQ.
[0056] Secondary Growth solution preparation 9.48 mM AA aq. AA (16.7 mg, 94.8 μmol) was dissolved in milliQ (10 mL).
[0057] AuNR Experimental Method Nuclear solution preparation (Seed solution) 2.4 mM HAuCl4 (0.5 mL, 1.2 μmol), 125 mM CTAB / milliQ (4.0 mL, 0.5 mmol), and 100 mM KBr aq. (0.5 mL, 00.05 mmol) were placed in a 10 mL glass sample bottle and vigorously stirred with a magnetic stirrer. After stirring, 10 mM NaBH4 (0.3 mL, 3.0 μmol) was added to the sample bottle and stirred for 2 min. After stirring, the mixture was mixed by inverting 7 times and left to stand in a thermostatic bath at 30°C for 1 h. This was used as the seed solution. Total Volume 5.3 mL Final Concentration [CTAB] = 94.34 mM [KBr] = 9.43 mM [HAuCl4 4H2O] = 0.226 mM [NaBH4] = 0.556 mM
[0058] Primary Growth Solution Preparation 122 mM CTAB aq. (77 mL, 9.41 mmol) was placed in a 250 mL glass medium bottle and stirred at room temperature using a magnetic stirrer. After stirring, 941 mM KBr aq. (1.0 mL, 0.941 mmol), 19.2 mM AgNO3 aq. (1.0 mL, 19.2 μmol), 4.60 mM HAuCl4 aq. (20 mL, 92.0 μmol), and 106 mM AA aq. (1.0 mL, 0.106 mmol) were added to the medium bottle, followed by Seed solution 1 (0.135 mL). This was used as the Primary Growth Solution. Total Volume 100.135 mL Final Concentration [CTAB] = 94.0 mM [KBr] = 9.40 mM [AgNO3] = 0.192 mM [HAuCl4 4H2O] = 0.919 mM [AA] = 1.05 mM [Au seed] = 0.305 μM
[0059] Secondary Growth solution preparation While vigorously stirring with a magnetic stirrer, 9.48 mM AA aq. (5.0 mL, 47.4 μmol) was added to the Primary Growth Solution using a microsyringe pump. The solution was then stirred for 10 min and stored at 25°C for 24 h. This was used as the Secondary Growth solution. Microsyringe pump conditions Syringe inner diameter: 17.0 mm Inflow volume: 5.00 mL Inflow rate: 1.75 mL / h Total Volume 105.135 mL Final Concentration [AA] = 0.451 mM [Au] = 0.88 mM (theoretical value)
[0060] AuNR purification After leaving it to stand for 24 hours, the Secondary Growth Solution was divided into six 50 mL PP centrifuge tubes, each containing approximately 17.5 mL. Next, the Secondary Growth Solution was centrifuged (10,000 rpm [9,840 xg], 30 min, 25°C), and the supernatant was removed. The precipitate was redispersed in milliQ to the same volume. This solution was designated AuNR / milliQ. Total Volume 105.135 mL Final Concentration [Au] = 0.88 mM (theoretical value)
[0061] 2. Synthesis of silica-coated AuNR containing fluorescent dye (SilicaAuNR@Fluorophore) Silica-coated AuNRs containing fluorescent dyes (SilicaAuNR@Fluorophore) were synthesized.
[0062] Samples used AuNR / milliQ ([Au] = 0.88 mM) Fluorophore used [Cationic] ·α,β,γ,δ-Tetrakis(1-methylpyridinium-4-yl)porphyrin p-toluenesulfonate (MW = 1363.60): TMPyP Rhodamine 6G (MW = 479.02): R6G [neutral] 7-Diethylamino-4-methylcoumarin (MW = 231.29): Coumarin 1 The concentration range of TMPyP and Coumarin 1 was set to 100-1000 μM. The concentration range of R6G was set to 0.1-1.0 μM.
[0063] Sample preparation Fluorescent dyes were prepared in 5.0 mL glass sample vials as follows. 4.0 mM TMPyP / MeOH (4.0 mL) 22.24 mg of TMPyP was filled into a 2.0 mL volumetric flask with MeOH and mixed by inversion 10 times. 4.0 mM R6G / MeOH (4.0 mL) 7.80 mg of R6G was filled into a 2.0 mL volumetric flask with MeOH and mixed by inverting 10 times. 4.0 mM Coumarin 1 / MeOH (4.0 mL) 3.77 mg of Coumarin 1 was filled into a 2.0 mL volumetric flask with MeOH and mixed by inverting 10 times.
[0064] Experimental Method AuNR / milliQ was added to a 15 mL PP centrifuge tube and centrifuged (8,000 rpm [6,011×g], 30 min, 25°C). After removing 1.25 mL of the supernatant, the mixture was redispersed with milliQ. Total Volume 105.135 mL Final Concentration [Au] = 1.17 mM
[0065] AuNR / milliQ (3.75 mL) was transferred to a 30 mL plastic wide-mouth bottle and stirred with a magnetic stirrer. After stirring, 0.1 M NaOH aq. (50 μL, 5 μmol) was added to the wide-mouth bottle containing AuNR, and each fluorescent dye / MeOH (1.25 mL) was added to the following final concentrations. Furthermore, 20 vol% TEOS / MeOH (15 μL) was added three times every 30 min (45 μL, 40.5 μmol), and then stirring was performed for 30 min. This solution was left to stand in a thermostatic bath at 25°C for 24 h. Total Volume 5.095 mL Final Concentration [Au] = 0.86 mM [NaOH] = 0.98 mM [TEOS] = 7.95 mM [TMPyP] = 100-1000 μM [R6G] = 0.1-1000 μM [Coumarin1] = 100-1000 μM
[0066] After 24 h, the solution was transferred to a 15 mL PP centrifuge tube and centrifuged (8,000 rpm [6,011×g], 30 min, 25℃), and the supernatant was removed. The precipitate was redispersed in MeOH of the same amount as the removed supernatant (approximately 5.095 mL). Furthermore, centrifugation (4,500 rpm [1,902×g], 30 min, 25℃) and supernatant removal were performed 3 to 16 times, and the precipitate was redispersed in MeOH of the same amount as the removed supernatant (approximately 5.095 mL). This solution was used as SilicaAuNR@Fluorophore. SilicaAuNR@Fluorophore in which the fluorescent dye is TMPyP is referred to as SilicaAuNR@TMPyP, SilicaAuNR@Fluorophore in which the fluorescent dye is R6G is referred to as SilicaAuNR@R6G, and SilicaAuNR@Fluorophore in which the fluorescent dye is Coumarin 1 is referred to as SilicaAuNR@Coumarin 1.
[0067] 3.FE-SEM image of SilicaAuNR@Fluorophore Figures 1A to 1C show the FE-SEM images of SilicaAuNR@TMPyP, SilicaAuNR@R6G, and SilicaAuNR@Coumarin 1, respectively. The interface silica coating of the gold nanorods was achieved even in the presence of cationic or neutral fluorescent dyes. The long axis, short axis, aspect ratio, and thickness of the silica layer of each SilicaAuNR@Fluorophore were determined from the FE-SEM images (the results are shown below). ·SilicaAuNR@TMPyP n=150 Long axis: 55.7±14.7nm Minor axis: 21.5±6.0nm Aspect ratio: 2.75±0.9 Silica layer: 21.1±4.1nm ·SilicaAuNR@R6G n=150 Long axis: 51.8±14.1nm Minor axis: 18.4±6.0 nm Aspect ratio: 3.08±1.1 Silica layer: 18.6±3.8nm ·SilicaAuNR@ Coumarin 1 n=150 Long axis: 76.9±8.8nm Minor axis: 28.9±5.9nm Aspect ratio: 2.8±0.6 Silica layer: 22.0±4.9nm
[0068] 4. Fluorescence Spectrum Measurement Fluorescence spectra were measured for SilicaAuNR@Fluorophore with three types of dyes (TMPyP, R6G, and Coumarin 1) that were confirmed to be silica-coated by FE-SEM observation. The measurement conditions for the fluorescence spectra are as follows. Measurement conditions Quartz cell, optical path length 1 cm, solvent: MeOH Excitation bandwidth 5 nm Fluorescence bandwidth: 20 nm Response Medium Sensitivity: High Final Concentration [Au] = 0.86 mM
[0069] Figure 2A shows the fluorescence spectrum (excitation wavelength: 424 nm) of SilicaAuNR@TMPyP. A fluorescence peak was observed at 658 nm for SilicaAuNR@TMPyP. Figure 2B shows the fluorescence spectrum (excitation wavelength: 528 nm) for SilicaAuNR@R6G. A fluorescence peak was observed at 550 nm for SilicaAuNR@R6G. Figure 2C shows the fluorescence spectrum (excitation wavelength: 375 nm) for SilicaAuNR@Coumarin 1. A fluorescence peak was observed at 448 nm for SilicaAuNR@Coumarin 1.
[0070] 5. Fluorescence observation by UV light (365 nm) irradiation SilicaAuNR@Fluorophore with three types of dyes (TMPyP, R6G, and Coumarin 1) introduced was irradiated with ultraviolet light using a UV transilluminator (wavelength 365 nm). Figure 3A shows a photograph of SilicaAuNR@TMPyP before ultraviolet light irradiation (upper row) and a photograph after irradiation (lower row). Figure 3B shows a photograph of SilicaAuNR@R6G before ultraviolet light irradiation (upper row) and a photograph after irradiation (lower row). Figure 3C shows a photograph of SilicaAuNR@ Coumarin 1 before ultraviolet light irradiation (upper row) and a photograph after irradiation (lower row). In each photograph, the vial on the right is a vial containing each SilicaAuNR@Fluorophore, and the other vials are vials containing the corresponding dyes (0 μM to 1000 μM). Fluorescence could be observed at the visual level for each SilicaAuNR@Fluorophore by UV irradiation.
[0071] 6. Photosensitization effect of SilicaAuNR@TMPyP The photosensitizing effect of TMPyP and SilicaAuNR@TMPyP was compared using 1,3-Diphenylisobenzofuran (DPBF). DPBF is a quencher that has no absorption in the wavelength region longer than 490 nm, and is decomposed by singlet oxygen, decreasing the absorption ability at the wavelength of 490 nm. Singlet oxygen is generated when a photosensitizer (such as TMPyP) reacts with ground-state oxygen using light energy.
[0072] Sample preparation 1.2 mM DPBF toluene solution 3.2 mg (0.012 mmol) of DPBF was dissolved in 10.0 mL of toluene. Since it is easily decomposed by light such as fluorescent light, the solution was immediately shielded from light with aluminum foil after preparation.
[0073] Comparison of photosensitization effects between TMPyP and SilicaAuNR@TMPyP SilicaAuNR@TMPyP ([TMPyP] = 0.75 μM) PhMe:MeOH = 9:1 solution (6 mL) was placed in a 30 mL glass sample bottle, and 1.2 mM DPBF toluene solution (100 μL) was added and mixed using a magnetic stirrer. The sample was irradiated with light using a light irradiation device equipped with various optical filters (Y-50 (500 nm ≦), R-60 (600 nm ≦), and R-66 (660 nm ≦)), and the change in absorbance at 416 nm was observed. The results are shown in Figure 4. Decomposition of DPBF by singlet oxygen was observed, and the efficiency of the photosensitizer-immobilized silica-coated gold nanorods was higher than that of the fluorescent dye alone.
Claims
1. Gold nanorods, a silica layer covering the entire gold nanorod; the silica layer comprises a fluorescent dye; the fluorescent dye is dispersed throughout the silica layer; Fluorescently labeled gold nanorods.
2. The fluorescently labeled gold nanorod of claim 1 , wherein the fluorescent dye is a cationic fluorescent dye or a neutral fluorescent dye.
3. the cationic fluorescent dye is α,β,γ,δ-tetrakis(1-methylpyridinium-4-yl)porphyrin p-toluenesulfonate (TMPyP) or its central metal complex, or rhodamine 6G (R6G); The neutral fluorescent dye is 7-diethylamino-4-methylcoumarin (Coumarin 1). The fluorescently labeled gold nanorod according to claim 2 .
4. A composition comprising the fluorescently labeled gold nanorods of claim 1.
5. the fluorescent dye is α,β,γ,δ-tetrakis(1-methylpyridinium-4-yl)porphyrin p-toluenesulfonate (TMPyP) or a central metal complex thereof; The composition is a composition for generating singlet oxygen upon irradiation with excitation light. The composition of claim 4.
6. A mixing step of mixing gold nanorods, alkoxysilane, and a fluorescent dye, A method for producing the fluorescently labeled gold nanorods described in claim 1.
7. The mixing step comprises: a first sub-mixing step of mixing the NaOH solution in which the gold nanorods are dispersed and the MeOH solution in which the fluorescent dye is dispersed; a second sub-mixing step of mixing the first mixed solution obtained in the first sub-mixing step with a MeOH solution having the alkoxysilane dissolved therein; 7. The method of claim 6, comprising:
8. The method according to claim 7, wherein the mixing step further comprises, after the second sub-mixing step, a warming and standing step of standing the second mixed solution obtained in the second sub-mixing step under a temperature condition of 20°C to 30°C for 12 to 36 hours.
Citation Information
Patent Citations
Labeled silica-coated gold nanorod and manufacturing method thereof
JP2021110734A